WoT Based Contamination Monitoring System (International Journal of Innovative Research in Computer Science & Technology, 2022)
Modernization and industrial  development are disrupting the contamination 's  equilibrium by releasing untreated harmful toxic elements  into the atmosphere, resulting in contamination of basic  ecosystem elements such as water, air, and soil, which are  necessary for humans to survive. The four major types of  contamination caused by industries are air contamination,  water contamination, and noise contamination. This  causes infections to spread through the air and water,  affecting both humans and animals. As a result,  controlling these pollutant characteristics is a major  undertaking. The major goal of this project is to design an  efficient and cost-effective industrial air, water, and sound  contamination monitoring system, and the main objective  of this paper is to provide an WoT-based industrial air,  water, and sound contamination monitoring system.  comprehensive mechanism to track the variables that are  causing the problem of contamination. This  project's/working system's technique is to read and track  pollutant indicators, as well as to inform when any of these  substances are released, contamination control authorities  are notified. Contamination levels are above industrial  requirements. The system looks into PH levels in  industrial effluents, CO levels, and other factors.CO2,  combustible gases, air humidity, and temperature During  the manufacturing process, minute optical dust particles  are released. as well as the sound level produced by the  industry, employing PH sensor, MQ6, MQ9, temperature  sensor, and other sensors Humidity, and noise sensors are  all included. This system is based on the Internet of Things  (WoT), which is a rapidly growing technology that  combines electronics and computer science. The Internet  of Things (WoT) concept allows us to obtain data from  faraway locations and preserve it in a database without  having to physically be present in that region.
Keywords: Air contamination; sound contamination; water contamination; WOT; sensors; monitoring system